THE LAW OF FOREST IN INDONESIA: PREVENTION AND SUPPRESSION OF FOREST FIRES - Gunadi, Ariawan; Gunardi, Gunardi; Martono, Martono (Bina Hukum Lingkungan, 2019)
Forests have significant function related biological diversity, habitat protection of flora fauna such as orangutan, tiger, elephant; climate-related functions such as carbon sequestration, air pollution; human settlements, human health, school activities, habitat for people, rural livelihoods; state defense as natural resources such as commercial industrial wood, non-wood forest products, international and national trade; ecotourism, and recreation. However the problem in Indonesia is forest fires. In order to maintain its functions, all the famers, forestry-concession owners, government, local government and private enterprise should prevent and suppress the forest fires through the existing law and regulations such as Constitution Law of 1945, Act Number 5 Year 1990, Act Number 22 Year 1999, Act Number 41 Year 1999, Act Number 1 Year 2009, Act Number 6 Year 1994 and Act Number 17 Year 2004 and aircraft operation conducted by foreign aircraft such as Australia, Canada, Malaysia, Russia and Singapore to assist Indonesian’s forest fires.